Preparation method of water-based NiOx nano-particles as well as product and application of water-based NiOx nano-particles

By adding ligands such as alcohol ethers to the surface of NiOx nanoparticles, and using room temperature reaction method and ball mill ultrasonic dispersion technology, the problems of poor dispersion and poor film formation in water were solved, and the photoconversion efficiency of perovskite solar cells was significantly improved.

CN119677304APending Publication Date: 2025-03-21XIAN POLYMER LIGHT TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839039.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

NiOx has poor dispersion and poor stability in water, and poor film formation on FTO substrates, resulting in low photoconversion efficiency of perovskite solar cells.

Method used

Alcohol ethers, alcohol amines, glycols, polyethylene glycols, etc. are used as surface ligands of nanomaterials to prepare aqueous NiOx nanoparticles through room temperature reaction method to control pH value and reaction time, and further improve the dispersion and film formation of nanoparticles through ball milling and ultrasonic dispersion technology.

Benefits of technology

The dispersion and stability of NiOx in water are improved, the film formation and light conversion efficiency on the FTO substrate are enhanced, and the process is environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677304A_ABST
    Figure CN119677304A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar cells, and provides a preparation method of water-soluble NiOx nano-particles and a product and application of the water-soluble NiOx nano-particles, the NiOx nano-particles are prepared by using one or more of alcohol ether, alcohol amine, glycol and polyethylene glycol as surface ligands of nano-materials and providing water-based groups (-OH and-NH2) and binding sites for chelating In and Sn on ITO (Indium Tin Oxide), and the water-soluble NiOx nano-particles are used for preparing the water-soluble NiOx nano-particles. The nano-particle comprises a NiOx inorganic substance and an organic ligand on the surface of the NiOx inorganic substance. The prepared NiOx dispersion liquid has relatively high oxygen affinity, relatively good leveling property, excellent film-forming property and relatively good spreadability, adhesive strength and compactness on an FTO (Fluorine-doped Tin Oxide) substrate; and the material is stable in storage and has excellent light conversion efficiency in the aspect of device performance. The whole reaction is carried out at room temperature, so that the method is green, environment-friendly and pollution-free, and dangers are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cells and relates to a water-based NiO x Nanoparticle preparation method, products and applications. Background Art

[0002] In an inverted perovskite solar cell, the hole transport layer is placed on the transparent electrode, followed by the light absorbing layer. The main advantage of this structure is that light first passes through the hole transport layer, which can make the cell have a smaller hysteresis and a higher filling rate, and the deposition of the electron transport layer does not affect the perovskite layer.

[0003] With the continuous development of science and technology, perovskite solar cells have broad development prospects because of their advantages such as high extreme conversion efficiency, low production cost, simple preparation process and high flexibility, which makes them applicable to photovoltaic power generation, LED and other fields.

[0004] NiOx is an important p-type semiconductor material with a band gap energy between 3.6-4.0 eV and a hole mobility between 0.1-3.0 cm 2 V -1 s -1 At the same time, NiO x As a commonly used hole transport layer material in inverse perovskite solar cells, it has the advantages of being cheap, stable and easy to prepare.

[0005] Conventional NiOx is prepared by sol-gel method. Its nanomaterial is calcined by Ni(OH)2 at 280℃. Its particle size is uneven and its water dispersibility is poor. It is difficult to form a film on FTO substrate and will form scattered stripes. x The prepared spin coating liquid is easy to precipitate and cannot be made into spin coating ink, which makes its light conversion efficiency on perovskite solar cells low, affecting its application in solar cells. Summary of the invention

[0006] The purpose of the present invention is to provide an aqueous NiO x Preparation method of nanoparticles and their products and applications to solve NiO x The technical problems include poor dispersibility in water, poor stability, poor film formation on FTO substrate, and low light conversion efficiency of the battery.

[0007] The technical solution of the present invention is as follows:

[0008] Aqueous NiO x The method for preparing nanoparticles comprises the following steps:

[0009] S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system;

[0010] S2. Under a temperature environment of 10-30° C., mixing the nickel salt and the first reaction system to obtain a second reaction system;

[0011] S3. Add alkali to the second reaction system, control the pH at 8-12, and react for 0.2-24h to obtain a Ni(OH)2 sol dispersion system;

[0012] S4. Centrifuge the Ni(OH)2 sol dispersion system and wash it several times with water until no anions are present;

[0013] S5. The product obtained in S4 is calcined at 230℃-300℃ for 1-24h to obtain black NiO x calcined body;

[0014] S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nanoparticles;

[0015] Furthermore, based on the amount of substance, the overall feed ratio of the nickel salt to the alkali is 1:(0.5-3).

[0016] Furthermore, the alcohol ether in S1 is a C3-C5 straight-chain alcohol ether, the alcohol amine is a C2-C5 straight-chain alcohol amine, the polyol is a C2-C6 glycol, and the polyethylene glycol is one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.

[0017] Furthermore, the volume ratio of the total volume of the alcohol ether, alcohol amine, glycol, and polyethylene glycol to the solvent in the first reaction system is (0.05-0.2):1.

[0018] Furthermore, the nanoparticles include NiO x Inorganic substances and NiO x The organic ligand on the surface of the inorganic substance is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol.

[0019] Furthermore, the total content of the organic ligands accounts for 5%-30% of the total weight of the nanoparticles.

[0020] Furthermore, the NiO x It comprises nickelous oxide and nickelous oxide, wherein the molar ratio of trivalent nickel to divalent nickel is (0.1-1):1.

[0021] Furthermore, the band gap of the nanoparticles is 3.6-4.0 eV.

[0022] Furthermore, the particle size of the nanoparticles is 3-10 nm.

[0023] Further, as mentioned above, aqueous NiOx Application of nanoparticles in the preparation of hole transport layers for perovskite solar cells.

[0024] The beneficial effects of the present invention are as follows:

[0025] The present invention uses one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol as surface ligands of nanomaterials to provide water-based groups (-OH, -NH2) so that NiO x It can be dispersed in water and can also provide binding sites that can chelate with In and Sn on ITO, so that the NiOx dispersion on the FTO substrate has higher oxygen affinity, better leveling, excellent film-forming, better spreadability, adhesion, and compactness; at the same time, NiO x The aqueous dispersion not only has long-term stability in terms of storage stability; but also has excellent light conversion efficiency in terms of device performance.

[0026] NiO of the present invention x During the synthesis, the ligands added to the solvent first provide a relatively strong chemical bond with Ni, such as Ni-N bond, Ni-O bond, and secondly control the particle size of the nanomaterial. The 3-5nm nanoparticles are spin-coated on the substrate to obtain the smallest surface defects. Thirdly, after high-temperature calcination, some ligands can still be retained to prevent aggregation in water and can be stably stored for more than one year. The shorter ligands on the surface of the nanoparticles minimize the distance between the nanoparticles on the spin-coated film, ultimately resulting in higher mobility and conductivity. The entire reaction is carried out at room temperature, which is green, environmentally friendly and pollution-free, avoiding the occurrence of danger. The ball milling process can reduce NiO x Powder particle size, shorten ultrasonic dispersion time, and promote the dispersion of nanoparticles in water. The mechanical vibration and cavitation effect of ultrasound are used to disperse nanoparticles in water efficiently and quickly. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 NiO prepared by the present invention x Schematic diagram of the nanoparticle structure.

[0028] Figure 2 NiO prepared by the present invention x TEM image of nanoparticles.

[0029] Figure 3 NiO prepared by the present invention x XRD pattern of nanoparticles.

[0030] Figure 4 NiO prepared by the present invention x UV-visible absorption graph of nanoparticles.

[0031] Figure 5NiO prepared by the present invention x Thermogravimetric analysis of nanoparticles. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be further described below through embodiments.

[0033] A method for preparing aqueous NiO x The method of producing nanoparticles comprises the following steps:

[0034] S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system;

[0035] S2. Under room temperature, the nickel salt and the first reaction system are mixed to obtain a second reaction system;

[0036] S3. Adding a base to the second reaction system, controlling the pH at 8-12, and reacting for 0.2-24h to obtain a Ni(OH)2 sol dispersion system;

[0037] S4. Centrifuge the Ni(OH)2 sol dispersion system and wash it several times with water until no anions are present;

[0038] S5. Calcine S4 at 230℃-300℃ for 1-24h to obtain black NiO x calcined body;

[0039] S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nanoparticles.

[0040] The above NiO x The nanoparticles can be ultrasonicated for 0.1-10h to obtain NiO x Nanoparticles in water.

[0041] The above room temperature refers to the temperature between 10-30℃;

[0042] The alcohol ether described in S1 above is a C3-C5 straight-chain alcohol ether. For example, one of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol propyl ether, propylene glycol methyl ether, and propylene glycol ethyl ether. The alcohol amine is a C2-C5 straight-chain alcohol amine, for example, one of ethanolamine, propanolamine, butanolamine, and pentanolamine. The polyol is a C2-C6 glycol, for example, one of ethylene glycol, diethylene glycol, and triethylene glycol.

[0043] The nickel salt in the above S1 can be selected from but not limited to nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel acetate and its hydrate, nickel sulfate and its hydrate, nickel bromide and its hydrate, nickel acetylacetonate and its hydrate, nickel dibutyl dithiocarbamate, nickel diethyl dithiocarbamate, nickel oxalate, nickel phosphate, nickel xanthate, nickel ethylenediaminetetraacetic acid, nickel isopropoxide, nickel 8-hydroxyquinoline, nickel stearate, nickel oleate, nickel hypophosphite and its hydrate, nickel fluoride, basic nickel carbonate, nickel perchlorate, nickel benzoate, nickel thiocyanate, and nickel trifluoromethanesulfonate.

[0044] The alkali in S3 can be selected from but not limited to one of ammonia water, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide and tetraethylammonium hydroxide.

[0045] The present invention also provides a NiO x Nanoparticles prepared according to the above method. NiO x Nanoparticles include NiO x Inorganic substances and NiO x Organic ligands on the surface. The organic ligands are one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol. NiO x When X in takes different values, it corresponds to divalent nickel and trivalent nickel respectively.

[0046] The band gap is calculated to be in the range of 3.6 eV-4.0 eV. The calculation method is well known to those skilled in the art, for example, it can be calculated by Tauc Plot method, which will not be described here. The size of the nanoparticles is in the range of 3-10 nm.

[0047] A perovskite solar cell comprises an anode, a hole transport layer, a light absorbing layer, an electron transport layer and a cathode, wherein the hole transport layer is made of the above-mentioned NiO x The nanoparticle aqueous dispersion is prepared by one of spin coating, printing, spray coating and blade coating.

[0048] Example 1: Ethanolamine as a surface ligand attached to NiO x The surface of nanoparticles

[0049] S1. Mix 50 ml of ethanolamine with 1 L of water to form a first reaction system;

[0050] S2. At 20°C, 0.25 mol of nickel nitrate is mixed with the first reaction system to obtain a second reaction system;

[0051] S3. A 4 mol / L aqueous NaOH solution was added to the second reaction system, the pH was controlled at 10, and the reaction was continued for 2 h to obtain a Ni(OH)2 green sol dispersion system;

[0052] S4. The Ni(OH)2 sol dispersion was centrifuged and washed with water three times until the nitrate ions were completely washed away;

[0053] S5. S4 was calcined at 280℃ for 2h to obtain black NiO x calcined body;

[0054] S6. NiO x The calcined body was ball milled in a ball mill for 12 h to obtain NiO x Nanoparticles.

[0055] NiO x The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.

[0056] Example 2: Ethanolamine and ethylene glycol methyl ether as surface ligands attached to NiO x The surface of nanoparticles

[0057] S1. 80 ml of ethanolamine, 20 ml of ethylene glycol methyl ether and 1 L of ethanol were mixed to form a first reaction system;

[0058] S2. At 15°C, 0.3 mol of nickel chloride is mixed with the first reaction system to obtain a second reaction system;

[0059] S3. Add 10% ammonia water by mass to the second reaction system, control the pH at 9, and react for 1 h to obtain a Ni(OH)2 sol dispersion system;

[0060] S4. The Ni(OH)2 sol dispersion was centrifuged and washed three times with water until the ammonium ions were completely washed away;

[0061] S5. S4 was calcined at 290 °C for 3 h to obtain black NiO x calcined body;

[0062] S6. NiO x The calcined body was ball milled in a ball mill for 3 h to obtain NiO x Nanoparticles.

[0063] NiO x The nanopowder was ultrasonicated for 0.5 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.

[0064] Example 3: n-Propanolamine, polyethylene glycol 200, and ethylene glycol as surface ligands attached to NiO x The surface of nanoparticles

[0065] S1. Mix 100 ml of n-propanolamine, 20 ml of polyethylene glycol 200, 1 ml of ethylene glycol and water to form a first reaction system;

[0066] S2. At 30°C, 0.3 mol of nickel sulfate is mixed with the first reaction system to obtain a second reaction system;

[0067] S3. A 4 mol / L aqueous solution of KOH was added to the second reaction system, the pH was controlled at 11, and the Ni(OH)2 sol dispersion system was obtained after the reaction for 1 h;

[0068] S4. The Ni(OH)2 sol dispersion was centrifuged and washed with water three times until the sulfate ions were eluted;

[0069] S5. S4 was calcined at 250℃ for 3.5h to obtain black NiO x calcined body;

[0070] S6. NiO x The calcined body was ball milled in a ball mill for 9 h to obtain NiO x Nanoparticles;

[0071] NiO x The nanopowder was ultrasonicated for 1.5 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.

[0072] Embodiment 4:

[0073] This embodiment provides a solar perovskite cell device, and its manufacturing method comprises: spin coating the NiO in embodiment 1 on the ITO anode layer; x The nanomaterial aqueous dispersion is then annealed at 120°C for 30 minutes to form a hole transport layer; the absorption layer is formed by spin coating a perovskite solution on the hole transport layer as a carrier; the isopropanol solution of zinc oxide is spin coated on the absorption layer and dried to form an electron transport layer; finally, the Au cathode electrode layer is evaporated and packaged to form a perovskite solar cell device.

[0074] Comparative Example 1:

[0075] S1. At 25°C, 0.3 mol of nickel nitrate and 1 L of water were mixed to obtain a first reaction system;

[0076] S2. 0.6 mol of NaOH aqueous solution was added to the first reaction system, and the reaction was continued for 2 h to obtain a Ni(OH)2 sol dispersion system;

[0077] S3. The Ni(OH)2 sol dispersion is centrifuged and washed twice with water until the nitrate ions are completely eluted;

[0078] S4. S4 was calcined at 280℃ for 1h to obtain black NiO x calcined body;

[0079] S5. NiOx The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.

[0080] Table 1: Comparison of device performance in various embodiments

[0081]

[0082] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. Aqueous NiO x A method for preparing nanoparticles, characterized in that: The following steps are involved: S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system; S2. Under a temperature environment of 10-30° C., mixing the nickel salt and the first reaction system to obtain a second reaction system; S3. Add alkali to the second reaction system, control the pH at 8-12, and react for 0.2-24h to obtain a Ni(OH)2 sol dispersion system; S4. Centrifuge the Ni(OH)2 sol dispersion system and wash it several times with water until no anions are present; S5. The product obtained in S4 is calcined at 230℃-300℃ for 1-24h to obtain black NiO x calcined body; S6. NiO x The calcined body is ball milled in a ball mill for 0.5-24h to obtain NiO x Nanoparticles.

2. Aqueous NiO according to claim 1 x The method for preparing nanoparticles is characterized by: Calculated by the amount of substance, the overall feed ratio of the nickel salt and the alkali is 1:(0.5-3).

3. Aqueous NiO according to claim 1 x The method for preparing nanoparticles is characterized by: The alcohol ether in S1 is a C3-C5 straight-chain alcohol ether, the alcohol amine is a C2-C5 straight-chain alcohol amine, the polyol is a C2-C6 glycol, and the polyethylene glycol is one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.

4. Aqueous NiO according to claim 1 x The method for preparing nanoparticles is characterized by: The volume ratio of the total volume of the alcohol ether, alcohol amine, glycol and polyethylene glycol to the solvent in the first reaction system is (0.05-0.2):

1.

5. Aqueous NiO prepared according to any one of the preparation methods of claims 1-5 x Nanoparticles, characterized in that: The nanoparticles include NiO x Inorganic substances and NiO x The organic ligand on the surface of the inorganic substance is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol.

6. NiO according to claim 6 x Nanoparticles, characterized in that: The total content of the organic ligands accounts for 5% to 30% of the total weight of the nanoparticles.

7. NiO according to claim 6 x Nanoparticles, characterized in that: The NiO x It comprises nickelous oxide and nickelous oxide, wherein the molar ratio of trivalent nickel to divalent nickel is (0.1-1):

1.

8. NiO according to claim 6 x Nanoparticles, characterized in that: The band gap of the nanoparticles is 3.6-4.0 eV.

9. NiO according to claim 6 x Nanoparticles, characterized in that: The particle size of the nanoparticles is 3-10 nm.

10. Aqueous NiO as claimed in claim 6 x Application of nanoparticles in the preparation of hole transport layers for perovskite solar cells.